Urgensi Program Parenting dalam Implementasi PAUD Inklusif - Jazariyah, Jazariyah (ACIECE, 2016)
This article is intended to express the importance of parenting programs in the implementation of inclusive early childhood education and how to maintenance this program in inclusive early childhood education. The results showed that the effectiveness of the implementation of an inclusive educationinfluenced by several aspects, one of which is the perception of parents. Parenting programs can be done through programs of early childhood education based on family, consisting of: 1) Group Parent Meeting (KPO), 2) The involvement of parents in the class (COD), 3) parental involvement in joint activities (KODAB), 4) Consulting day (HK) and Home Visit (KR). The importance of parenting program areto have the same vision, so the schools are easily organize programs that will be implemented. Parenting can also broaden childcare. The parenting program is expected to have an impact on the internalization of an inclusive vision of the child continously. So that someday the kids will have the respect and peace with diversity from an early age.